Arabic Language Education Madrasah Ibtidaiyah With A Humanitarian Perspective: ITS Concept, Implementation and Challenges In The Digital Era - Novia Dwi Nurcahyaningtias; Binti Susila Wati; Aulia Irfiana (Universitas Al-Amien Prenduan, 2026)
Arabic Language Education at Madrasah Ibtidaiyah has a strategic role in developing linguistic competence as well as shaping the character of students through the internalization of Islamic and humanitarian values. The development of the digital era requires that learning Arabic is not only oriented towards mastering linguistic aspects, but also being able to develop critical thinking, communication, collaboration, and student character skills through a humanist and contextual approach. This study aims to analyze the concept of Arabic education from a humanitarian perspective, describe its implementation in learning in the digital era, and identify various challenges faced in its application in Madrasah Ibtidaiyah. The research uses a descriptive qualitative approach carried out at Madrasah Ibtidaiyah Integrated Thoriqul Jannah. The research informants consisted of madrasah heads, Arabic teachers, and students in grades IV to VI who were selected by purposive sampling. Data were collected through observation, in-depth interviews, documentation, and literature studies. Data analysis uses the Miles, Huberman, and Saldaña interactive analysis model which includes data condensation, data presentation, and conclusion extraction and verification, while data validity is tested through source triangulation, technique triangulation, and member checking. The results of the study show that Arabic education from a humanitarian perspective is applied through student-centered learning by utilizing communicative, collaborative, and contextual strategies, such as language games, simple dialogue (muḥādatsah), project-based learning, and the use of interactive digital media. The implementation not only improves Arabic language competence, but also fosters empathy, responsibility, cooperation, tolerance, and confidence of students. However, its implementation still faces various challenges, including the limitation of teachers' competence in applying humanistic approaches, the lack of innovative learning media, the influence of digital culture on learning motivation, and the limitations of learning facilities and infrastructure. Therefore, it is necessary to improve teacher competence, develop innovative learning media, strengthen character-based curriculum, and provide adequate educational facilities so that Arabic education from a humanitarian perspective can be applied optimally in Madrasah Ibtidaiyah. Keywords: Arabic Language Education, Madrasah Ibtidaiyah, humanitarian perspective, humanistic learning, digital era.